Karakteristik Komponen Tepung Dalugha (Cyrtosperma Merkusii) Dan Sagu Tanah (Tacca Leontopetaloides L.Kanzt) - Mege, Revelson A.; Moko, Emma Mauren; Lensehe, Febby Anggini (Universitas Negeri Manado, 2020)
The dalugha tuber (cyrtosperma merkussi) and the sago tanah (tacca leontopetaloides l.kantz) are potential alternative sources of food in northern sulawesi who have not been fully informed of their characteristics, so it is necessary to characterize the composition chemical and physical of dalugha flour and sago soil given the potential of trade as a potential alternative food source in northern sulawes. non-rice food sources. The aim of this study was to obtain the physicochemical characteristics and properties of dalugha and sago bulbs bulb flour. Advantages which can be obtained from the results of this study, namely: information on the knowledge of the characteristics of the components of dalugha flour (cyrtosperma merkusii) and of ground sago (tacca leontopetaloides l.kantz) so that it can be used as alternative food ingredient for tubers. The results showed that the chemical analysis of dalugha flour is an average water content of 29.08 gr, an ash content of 0.60 gr, a fat content of 0.42 gr, a protein content 0.34 gr, carbohydrates 69.56 gr, amylose 29, 64 gr, amylopectin 32.88 gr and Soil sago i.e. water content 39.98 gr, ash content 0.07 gr, fat 0.22 gr, protein content 0.21 gr, carbohydrates 59.52 gr, amylose 29.08 gr, amylopectin 24.00 gr.Â Keywords: dalugha tubers, soil sago, flour, characteristics.